Sustainable grafted chitosan-dialdehyde cellulose with high adsorption capacity of heavy metal - Essam S. Abd El-Sayed; Sawsan Dacrory; Hisham A. Essawy; Hanan S. Ibrahim; Nabila S. Ammar; Samir Kamel (BMC Chemistry, 2023)
Abstract A novel adsorbent was prepared using a backbone comprising chemically hybridized dialdehyde cellulose (DAC) with chitosan via Schiff base reaction, followed by graft copolymerization of acrylic acid. Fourier transform infrared spectroscopy (FTIR) confirmed the hybridization while scanning electron microscopy (SEM) revealed intensive covering of chitosan onto the surface of DAC. At the same time, energy dispersive X-ray (EDX) proved the emergence of nitrogen derived from chitosan. The X-ray diffraction (XRD) indicated that the crystallinity of the backbone and graft copolymer structures was neither affected post the hybridization nor the grafting polymerization. The adsorbent showed high swelling capacity (872%) and highly efficient removal and selectivity of Ni2+ in the presence of other disturbing ions such as Pb2+ or Cu2+. The kinetic study found that the second-order kinetic model could better describe the adsorption process of (Cu2+, Ni2+) on the graft copolymer. In contrast, the first-order kinetic model prevails for the binary mixture (Pb2+, Ni2+). Moreover, the correlation coefficient values for the adsorption process of these binary elements using Langmuir and Freundlich isotherms confirmed that the developed grafted DAC/chitosan exhibits a good fit with both isotherm models, which indicates its broadened and complicated structure. Furthermore, the grafted DAC/chitosan exhibited high efficient regeneration and high adsorption capacity for Pb2+, Cu2+ and Ni2+.